Relationship Between Height and Smash Accuracy in Volleyball for Students at SMK Negeri 1 Bancak (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study investigates the relationship between height and volleyball smash accuracy among 11th-grade students at SMK Negeri 1 Bancak. Using a quantitative correlational design, data were collected from 30 students selected through purposive sampling. Height was measured using a stature meter, while smash accuracy was assessed through a targeted zone test on a volleyball court, with each participant performing ten attempts. Data were analyzed using Pearson’s Product–Moment correlation after confirming normal distribution via the Shapiro–Wilk test. The results revealed a moderate, positive, and statistically significant correlation between height and smash accuracy (r = 0.532, p = 0.003). These findings indicate that taller players tend to achieve higher smash accuracy, likely due to advantages in reach and attack angle, which facilitate steeper and more difficult-to-defend shots. Nonetheless, height is not the sole determinant of performance; technique, strength, coordination, and experience also play vital roles. This study provides empirical evidence relevant to school-level volleyball coaching, suggesting that training programs should optimize both anthropometric advantages and technical skills to enhance overall performance.